The mycorrhizal pathway of zinc uptake contributes to zinc accumulation in barley and wheat grain - Antonio Coccina (BMC Plant Biology, 2019)
Abstract Background Increasing zinc (Zn) concentrations in crops is important for alleviation of human Zn deficiency. Arbuscular mycorrhizal fungi (AMF) contribute to plant Zn uptake, but their contribution to Zn in the edible portion of crops has not yet been investigated. This study aimed to quantify the mycorrhizal pathway of Zn uptake into grain of wheat and barley under varying soil Zn availabilities. Bread wheat (Triticum aestivum) and barley (Hordeum vulgare) were grown in pots with a hyphal compartment containing 65Zn. Plants were inoculated with Rhizophagus irregularis and grown at three soil Zn concentrations. Radioactive Zn in grain and straw was measured and the contribution of AMF to Zn uptake was calculated. Results The mycorrhizal pathway of Zn uptake contributed up to 24.3% of total above-ground Zn in wheat, and up to 12.7% of that Zn in barley. The greatest contribution by the mycorrhizal pathway was observed in barley at the lowest Zn addition, and in wheat at the highest one. In addition, grain yield of bread wheat was increased by AMF. Conclusions These results suggest that AMF have a substantial role in uptake of Zn into cereals, and the proportional contribution by the MPU is dependent on plant species, as well as available soil Zn.